Demographic differences in Canadian medical students' motivation and confidence to promote physical activity. (4th July 2019) - McFadden, Taylor; Fortier, Michelle; McGinn, Ryan; Levac, Brendan M; Sweet, Shane N; Tomasone, Jennifer R
Abstract: Background: Physical activity (PA) remains under prescribed by physicians. Motivation and confidence are clear drivers of frequency of promoting PA. Research shows demographic differences in physicians' preventive practices, yet none have included medical students who form habits during training. Objectives: Study objectives were to (i) examine how Canadian medical students' motivation to recommend PA to future patients differs according to six demographic variables (i.e. gender, ethnicity, year of study, university, proposed specialty and academic background) and (ii) examine how Canadian medical students' confidence to recommend PA to future patients differs according to these same demographic variables. Methods: A cross-sectional design was used. First to fourth year medical students from three medical schools responded to an online survey ( N = 221). Results: Female participants were more motivated to counsel patients on PA and refer to an exercise specialist compared to males ( P < 0.01). Second year students were more motivated to assess a patients' level of PA compared to third and fourth year students ( P < 0.01). Students pursuing family medicine were more confident to assess and counsel compared to students pursuing paediatrics ( P < 0.01). Conclusion: Given that motivation and confidence have a positive influence on frequency-promoting PA, these results suggest where future efforts should focus, to improve PA promotion in medical practice. Physical inactivity continues to be a major issue worldwide, and medical students as future physicians have a unique opportunity to enhance PA amongst the population.